2015
DOI: 10.1128/mbio.02018-14
|View full text |Cite
|
Sign up to set email alerts
|

The Cellobiose Sensor CebR Is the Gatekeeper of Streptomyces scabies Pathogenicity

Abstract: A relatively small number of species in the large genus Streptomyces are pathogenic; the best characterized of these is Streptomyces scabies. The pathogenicity of S. scabies strains is dependent on the production of the nitrated diketopiperazine thaxtomin A, which is a potent plant cellulose synthesis inhibitor. Much is known about the genetic loci associated with plant virulence; however, the molecular mechanisms by which S. scabies triggers expression of thaxtomin biosynthetic genes, beyond the pathway-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(109 citation statements)
references
References 34 publications
2
107
0
Order By: Relevance
“…The data represent the average molecular weight for the entire polymer distribution. environment [Francis et al, 2015]. Actually, the environment in the human oral cavity is highly variable, especially with respect to pH, osmolarity, and oxygen content, which fluctuate throughout the dental plaque biofilm [Crepps et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
“…The data represent the average molecular weight for the entire polymer distribution. environment [Francis et al, 2015]. Actually, the environment in the human oral cavity is highly variable, especially with respect to pH, osmolarity, and oxygen content, which fluctuate throughout the dental plaque biofilm [Crepps et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
“…This delay in the response of BG might be a consequence of the delay in (Glc) 3 consumption observed for the ΔbglC strain (Fig. A), but also because (Glc) 3 is a much weaker allosteric effector of CebR relative to (Glc) 2 (Francis et al ., ). These observations demonstrate that BglC is not the only functional BG in S. scabies to catabolize cello‐oligosaccharides.…”
Section: Resultsmentioning
confidence: 97%
“…scabies . We generated a bglC null mutant (Δ bglC ) by replacing orf scab57721 with the apramycin resistance cassette, as performed previously for cebR , cebE and msiK (Francis et al ., ; Jourdan et al ., ). Semi‐quantitative analysis by high‐performance liquid chromatography (HPLC) revealed that the Δ bglC /Δ 57721 mutant produced only 37% and 9% of the thaxtomin levels produced by the wild‐type strain when cultivated in liquid minimal medium (MM) with (Glc) 2 or (Glc) 3 as sole carbon source, respectively (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Remarkably, the expression of some of the pathogenicity genes, including those for the phytotoxin thaxtomin, is determined in part by the cellobiose sensor CebR, the universal regulator of Streptomyces cellulolytic genes, integrating pathogenicity-linked cellulolytic activity with more ancient overall responses to cellulose-related metabolites 36 . The connection of pathogenicity with cellulose is further emphasised by the fact that thaxtomin is an inhibitor of plant cellulose synthase.…”
Section: Ecology and Evolutionmentioning
confidence: 99%